PENEGAKAN HUKUM TERHADAP PENGENDARA YANG MENGAKIBATKAN KECELAKAAN LALU LINTAS DENGAN KORBAN MENINGGAL DUNIA (Studi Putusan Nomor. 734/PID.SUS/2023/PN LBP) - Subur Pranoto, Ismed Batubara (NERACA KEADILAN, 2024)
A traffic violation is a violation of traffic laws and regulations and for people who are subject to criminal sanctions and the case filing process uses a quick examination procedure in accordance with Articles 207, 211 and 216 of the Criminal Procedure Code. The type of research used in this research is empirical legal research, namely legal research carried out by examining library materials or secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The location for data collection in this research was at the Gakkum Unit of the Traffic Unit of the Deli Serdang Police, which is located in Diponegoro, Lubuk Pakam - Deli Serdang. The technique of designating a word that is abstract and not manifested in an object, but its use can only be seen through: questionnaires, interviews, observations, examinations (tests), documentation, etc. Based on a report from the Head of the Deli Serdang Police Traffic Unit, the main factors causing traffic accidents in Deli Serdang Regency involve several crucial aspects. The influence of alcohol is one of the main causes, where drunk drivers tend to experience decreased driving abilities, such as poor judgment and slow reflexes. In the provisions of Law no. 22 of 2009, which is contained in Article 25 which states that every road used for public traffic must be equipped with road equipment in the form of traffic signs, road markings, traffic signaling devices, street lighting devices, control and safety devices for road users, equipment road monitoring and security, facilities for bicycles, pedestrians and people with disabilities, supporting facilities for traffic and road transportation activities on the road and outside the road. Tge result od reseaech conclude that has been carried out, it can be concluded that traffic crimes, including traffic accidents, are serious violations of traffic regulations that can result in harm to individuals and society. Traffic accidents can be caused by various factors such as driver negligence, poor road conditions, and unfit vehicles. According to Law Number 22 of 2009 concerning Road Traffic and Transportation, traffic accidents are unexpected and unintentional events involving vehicles and can result in human casualties and property loss. These accidents are grouped into light, medium and severe categories based on their impact.